PENERAPAN MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN KREATIVITAS SISWA PADA MUATAN PELAJARAN IPS KELAS IV MADRASAH IBTIDAIYAH - Tahrid (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
This research aims to increase student creativity through the Inquiry Learning Model in class IV social studies content at MI NW Dasan Agung. The type of research used is classroom action research (PTK), which is carried out in 2 cycles, each cycle consisting of 2 meetings and going through several stages such as the planning stage, action stage, observation stage. and reflection (reflecting). while data collection techniques use Observation Sheets, Questionnaires, and Documentation. The results of this research show that the use of the Inquiry Learning Model can increase student creativity. This can be seen from the results of the questionnaire data obtained by students, student creativity using the Inquiry Learning Model has increased from cycle I to cycle II, in cycle I the percentage obtained reached 47.26%, while after improvements were made in cycle II, then the percentage obtained was 89.9% in the very good category. so it is clear that the application of the Inquiry Learning Model in social studies content can increase the creativity of class IV students at MI NW Dasan Agung, Mataram City.